EXPLORING THE EFFECT OF ORGANIC ADDITIVES ON PHYSICAL PROPERTIES OF BITUMEN (Advances in Civil and Architectural Engineering, 2022)
Warm additives had wide popularity in recent years due to saving in energy and lowering emissions dealt with asphalt mixture production. Warm Mix Asphalt (WMA) is produced by using foaming technology or reducing -viscosity additives of binder to enhance the rheological properties. In this study, organic-based additives (Asphaltan A and Asphaltan B) are used to investigate their effect to minimize the viscosity and lower the temperature of asphalt mixture production. Bitumen is mixed with three doses of each additive: 1, 2, and 3% of its weight. The binder viscosity was measured by rotational viscometer with and without the additives at three different temperatures. The study showed that the organic additives have a positive impact on the behavior of the binder in terms of viscosity reduction and made enhancements in terms of bitumen properties. This result could be useful in the reduction of production temperature and quantity of odour emissions.